Business Plan ProBlend & Co. / Nur Syafiqah Abdul Malek - Abdul Malek, Nur Syafiqah (2020)
We will choose to develop a business that sells portable blender. Our portable blender that also known as ProBlend. Our portable blender is a fundamental piece of any kitchen, regardless of whether you're making juice, milkshakes, smoothies and margaritas or pureeing summer tomatoes from the patio nursery for custom made marinara or any other types of foods or drinks. In spite of the ubiquity of nourishment processors and hand or drenching blenders, this portable blenders are also as yet the best decision for smashing ice, preparing a smoothie or other solidified beverage and pureeing soups. Utilize this blender purchasing manual for assistance you locate the best blender for the majority of your culinary assignments. Now, you can make your favorite smoothies on the go, at the gym, at the library, on your routine morning jogs, at the beach or right in your dinning! Be anywhere. Blend everywhere with our ProBlend portable blender.